Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution. (January 2023) - Li, Yue-Jun; Gao, Yong-Jin; Zhou, Hui; Zhang, Guang-Ya; Wen, Lei; Zhao, Yan; Li, Cheng; Zheng, Duo-Ming; Liu, Ya-Lei; Li, Hong-Hui; Luo, Cai-Ming; Huang, Tong-Fei; et al.
Graphical abstract: Highlights: Well-preserved Early Paleozoic collision related structures were discovered in the Tarim Basin. Both collision and accretion occurred in the Proto-Tethys. Collision-related structures are significant for the study of collisional orogenic belt. The Altun is an Early Paleozoic accretion-collision orogenic belt. The West Kunlun is a long-lived Early Paleozoic accretionary orogenic belt. Abstract: The Tarim-Qaidam collision occurred along the southeastern margin of the Tarim Craton in the Early Paleozoic. This collision resulted in the formation of the Altun Suture, a Proto-Tethyan suture. It is one of the northernmost suture zones in the Tethysides. This Proto-Tethyan suture was not re-opened during the period of Paleo- and NeoTethyan history, and, of course, no Paleo- or NeoTethyan suture was superimposed on it. The collision-related structures in response to this collision are well-preserved in the Tarim Basin. They were discovered during our careful seismic interpretation. The syn -collision structures mainly include a foreland fold-thrust belt (the Tangguzibas foreland fold-thrust belt) and three large basement-involved anticlines (the Lunnan, Tadong and Tazhong anticlines). While the post-collision structures are a series of normal faults and their combinations of en echelon fault zones. From the deformation characteristics of these syn -collision structures, it was inferred that their related collision occurred in the southeastern margin of the Tarim Craton. It is the Tarim-Qaidam collision which resulted in the formation of the Early Paleozoic Altun Suture. Analyzing the growth strata, unconformities, fault growth index and the strata involved in the collision-related deformation, the syn -collision structures were formed in the Late Ordovician to Early Silurian, and the post-collision structures in the Middle Silurian to Middle Devonian. It can be fairly deduced that the Tarim-Qaidam collision initiated in the Late Ordovician, lasted to the Early Silurian, and then evolved into the post-collision extensional stage of the Middle Silurian–Middle Devonian.